The Development of Fiqh Teaching Materials with English-Language Visuals Based on Google Sites - Siti Rahma Dongoran; Muhammad Darwis Dasopang; Hamka Hamka (IICET (Indonesian Institute for Counseling, Education and Therapy), 2025)
The delivery of monotonous and less varied material, as well as the limited availability of teaching materials that can integrate technology and visualizations in a foreign language, has become an obstacle in improving students' motivation and understanding. Therefore, it is necessary to develop innovative, interactive, and relevant teaching materials that meet the needs of students in the digital era. The use of Google Sites-based media, equipped with images in English, is expected to enrich the learning experience and increase students' interest in understanding Fiqh material. This study aims to develop Fiqh teaching materials based on Google Sites equipped with English-language images, and to examine the feasibility and effectiveness of these materials in the learning process at MTsN 1 Padangsidimpuan. This research employed a Research and Development (R&D) method using the 4D development model, which consists of the Define, Design, Develop, and Disseminate stages. The results of the study indicate that the developed teaching materials received an excellent rating from media experts, material experts, and language experts with an average feasibility percentage of 93.78%. Statistical tests showed a P-value of 0.0000, indicating that the use of Google Sites-based teaching materials had a significant impact on improving students' learning outcomes. Positive student responses also supported this finding, as they felt that the learning process became more interesting, easily accessible, and helped them better understand the material. These teaching materials contribute significantly to providing innovative, effective Fiqh learning media that also support the strengthening of foreign language literacy in the context of madrasah education.